2019
DOI: 10.2147/btt.s204726
|View full text |Cite
|
Sign up to set email alerts
|

<p>Recurrent ruptured abdominal aneurysms in polyarteritis nodosa successfully treated with infliximab</p>

Abstract: Systemic polyarteritis nodosa (PAN) is a rare form of necrotizing vasculitis in children. Recurrent episodes of abdominal aneurysm ruptures are uncommon and life-threatening condition in children. Failures of response to immunosuppressive medications and radiological intervention also lead to high mortality. Some reports suggested that tumor necrosis factor (TNF) might have role in the inflammation of this disease. After an English-language literature review, this is the first case report in children of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Her disease resisted conventional treatment, including steroids, cyclophosphamide and intravenous immunoglobulins, and she developed recurrent‐ruptured aneurysms in the GI tract. After a temporary improvement, resulting from arterial embolisation during angiography, infliximab was initiated and the disease remitted 36 …”
Section: Resultsmentioning
confidence: 99%
“…Her disease resisted conventional treatment, including steroids, cyclophosphamide and intravenous immunoglobulins, and she developed recurrent‐ruptured aneurysms in the GI tract. After a temporary improvement, resulting from arterial embolisation during angiography, infliximab was initiated and the disease remitted 36 …”
Section: Resultsmentioning
confidence: 99%
“…A review of 11 reports showed that severe, life-threatening GI involvement was found as small intestinal stricture, enteritis, colitis, ischemic necrosis, and its complications, such as obstruction, perforation, peritonitis, and mesenteric infarction. 21 , [23][24][25][26][27][28][29][30][31][32] These pediatric patients with PAN who presented with aneurysms with or without rupture are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…These results, specific to this patient, differ from other studies of bulk RNA sequencing on intracranial aneurysm tissue that implicates B-lymphocytes in aneurysm rupture ( 35 ). Future studies will be needed to demonstrate the causation and disease modification with the immunomodulating therapies, such as with the anti-TNFα monoclonal antibody infliximab, that has already shown promise in the treatment of extracranial aneurysms for the patients with polyarteritis nodosa ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%